The Powers of the Supervisory Body in the GDPR as a Basis for Shaping the Practices of Personal Data Processing - Hajduk, Paweł (Review of European and Comparative Law (Online), 2021)
The purpose of this article is to analyse the competences of the supervisory authority provided for in the General Data Protection Regulation (GDPR) as a tool to shape the practice of personal data processing. This article verifies the thesis that the status of the supervisory authority formed in the GDPR, taking into account the authority’s independence, makes it possible to exercise the authority thoroughly, which is the basis for shaping personal data processing practice. Supervisory authorities have a wide range of powers to carry out the duties assigned to them. This is guaranteed by their independence. The exercise of powers resonates with all entities that fall under the jurisdiction of those authorities. The decisions of the authorities become the subject of interest of both the literature and personal data administrators. The powers connected with imposing administrative penalties might play a particular role. Their imposition causes that entities which are in similar circumstances may expect to be subject to the same penalties. In order to avoid this situation, they tend to adapt their practices to the model adopted in the decision. Opinions and recommendations, as well as codes of conduct approved by the supervisory authorities for particular sectors, which are a benchmark for administrators in those sectors, play an important preventive role.